Why are the G-20 Data Gaps Initiative and the SDDS Plus Relevant for Financial Stability Analysis? - Heath, Robert (IMF Working Papers; Working Paper ;, 2013)
In the wake of the recent global crisis the international community is giving an increased focus on stability of the financial system, so-called financial stability analysis. With the increasing need for data sets to undertake this analysis, the question naturally arises as to what types of data are needed? While various data initiatives are underway, two initiatives at the forefront are: (1) the IMF/FSB G-20 Data Gaps Initiative (DGI) created by the international statistical community and endorsed by the G-20 Finance Ministers and Central Bank Governors as well as the IMF's International Monetary and Financial Committee, and (2) the new Special Data Dissemination Standard Plus (SDDS Plus), aimed particularly at economies with systemically important financial sectors. This paper explains the relevance of the DGI for financial stability analysis and the close link with the SDDS Plus. The importance of the SDDS Plus in promoting the dissemination to the public of a core set of data for financial stability analysis is emphasized.